2015
DOI: 10.4038/jrrisl.v95i0.1836
|View full text |Cite
|
Sign up to set email alerts
|

Insight into prevention of enzymatic browning and increase of antioxidant potential of crepe rubber with ethephon stimulation

Abstract: The effect of different ethephon concentrations 1%-5% (w/v) on colour of crepe rubber and plasticity retention index (PRI) was studied. The study was conducted with the RRISL 121 clone using S/2, d3 harvesting system. The results revealed that ethephon stimulation affects strongly the antioxidant and polyphenol oxidase (PPO) inhibitory potential. Further, thiol content and PRI values were increased while giving low Lovibond colour index upto 3% ethephon concentration and the properties were found to be inferio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It was also reported that polyphenols, proteins, and carotenoids are the coloring constituents in NR latex [17]. The concentration of polyphenols, proteins, and carotenoids in the NR latex were 2 × 10 −2 , 1, and 3 × 10 −5 (w/w), respectively, and their contribution to the total absorptivity in the yellow-brown region were 2.3, 0.1, and 0.01%, respectively [18]. After processing the NR latex into the dry rubber, the residual color substances continue to be oxidized by heat to generate a variety of yellow oxides; the value of the color index with the clones and processing parameters are very different.…”
Section: Composition and Biosynthesis Of Color Substancesmentioning
confidence: 85%
See 2 more Smart Citations
“…It was also reported that polyphenols, proteins, and carotenoids are the coloring constituents in NR latex [17]. The concentration of polyphenols, proteins, and carotenoids in the NR latex were 2 × 10 −2 , 1, and 3 × 10 −5 (w/w), respectively, and their contribution to the total absorptivity in the yellow-brown region were 2.3, 0.1, and 0.01%, respectively [18]. After processing the NR latex into the dry rubber, the residual color substances continue to be oxidized by heat to generate a variety of yellow oxides; the value of the color index with the clones and processing parameters are very different.…”
Section: Composition and Biosynthesis Of Color Substancesmentioning
confidence: 85%
“…Ethephon treated 1-3% samples showed significantly low Lovibond color index (lighter color), and overdosage may lead to discoloration. Lighter-colored rubber is also obtained by adding glutathione at the latex stage to replace the toxic bleach [18]. The first is to obtain high-quality white NR latex from the control source.…”
Section: Biologically Controlled Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] The prevention of enzymatic browning in NR by stimulation Hevea tree with optimum concentration of ethephon has been reported. [ 13 ] The ethephon increased the content of thiol of the latex which acted as antioxidant by reacting with phenolic compound to form colorless products. A decrease of PPO activity in latexes at the first tapping after stimulation has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Sakdapipanich, 2022 the polyphenol react with oxygen in the presence of polyphenol oxidase. When these quinines react with amino acids and proteins, colourants will form (Attanayake et al, 2015). It has been shown that the fractionation process of the latexm obtained from the RRISL 203 clone yields white colour crepe rubber compared to the widely used clones in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%